La creatività digitale: ripensare una categoria estetica - Cecchi, Dario (Aesthetica Preprint, 2023)
The article aims at reconsidering the category of creativity from different operative perspectives: design and motion pictures above all. The philosophical framework of the paper is the Kantian philosophy, as the latter is interpreted and newly formulated by the Italian philosopher Emilio Garroni, who pays a particular attention to the role played by the Critique of Judgment within the transcendental philosophy. In this light, creativity appears as neither a creation e nihilo, nor as the pure accomplishment of the natural world, as other theories of art have argued. Creativity displays the faculty of dealing with rules in a free way, so that new possibilities are left open to the human form of life. This idea of creativity seems to be especially adequate to understand the way the European culture has developed its own creative potentialities throughout its long-lasting history.